2018
DOI: 10.3389/fphar.2018.00891
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Serum and Fecal Metabolomics Study of Collagen-Induced Arthritis Rats and the Therapeutic Effects of the Zushima Tablet

Abstract: The Zushima tablet (ZT) has been used for decades in the clinical treatment of rheumatoid arthritis (RA) in China. However, its therapeutic mechanism is unclear. In this study, we aimed to explore the distinctive metabolic patterns in collagen-induced arthritis (CIA) rats and evaluate the therapeutic effects of ZT on RA using untargeted serum and fecal metabolomics approaches based on gas chromatography coupled with mass spectrometry. Body weight, hind paw swelling, TNF-α and IL-1β levels, arthritis scores, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 42 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…However, the underlying mechanisms and targets are open to be explained. Our results of untargeted metabolomics combined with UPLC-MS determined not only the differentially isolated metabolites from blood serum and tissues, but also the GERA extract [10][11] . Figures 3 and 4 showed differentially isolated metabolites between three propositions of GERA, while enrichment analysis of KEGG pathways displayed the overall differential metabolites were majorly involved in iso avonoid biosynthesis and biosynthesis of unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 86%
“…However, the underlying mechanisms and targets are open to be explained. Our results of untargeted metabolomics combined with UPLC-MS determined not only the differentially isolated metabolites from blood serum and tissues, but also the GERA extract [10][11] . Figures 3 and 4 showed differentially isolated metabolites between three propositions of GERA, while enrichment analysis of KEGG pathways displayed the overall differential metabolites were majorly involved in iso avonoid biosynthesis and biosynthesis of unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 86%
“…exhibited decreased numbers of inflammatory monocytes and CD11c + Ly6c + cells and reduced levels of proinflammatory monocyte chemotactic protein- (MCP-) 1 and MCP-3 [ 87 ]. In a recent metabolomic study, altered metabolites contained citric acid and l-isoleucine both in the serum and in the faeces were identified in rats with CIA compared with the control rats [ 88 ]. Jubair et al found that in the CIA model, the absence of a dominant microbiota resulted in an approximately 40% reduction in disease severity through the regulation of mucosal and systemic cytokines and autoantibodies, and gut microbial dysbiosis was associated with the mucosal Th17 immune response, stimulating mucosal lymphoid tissue-producing autoantibodies and regulating autoantibody effector functions in the preclinical phase of CIA [ 89 ].…”
Section: Gut Microbiota and Metabolites In Ramentioning
confidence: 99%
“…Qingluo Tongbi decoction (QLT) had a beneficial effect on altered bacterial genera and families (Lachnospiraceae, Eubacteriaceae, and Leuconostocaceae) in rats with adjuvant-induced arthritis (AA) and significantly decreased the expression levels of cadherin-11, IL-17 α , TLR2, and TLR4 in synovial tissues, which negatively correlated with the abundance of Staphylococcus and Candidatus_Saccharimonas [ 114 ]. The families of bacteria in the faeces and the metabolites in both the serum and faeces were altered in rats with CIA, and the Zushima tablet (ZT) restored most of these metabolites (including l-isoleucine, l-aspartic acid, pyruvic acid, cholic acid, and hypoxanthine) and bacteria (such as Coriobacteriaceae, Bacteroidaceae, and Porphyromonadaceae) [ 88 ]. The route of administration may also influence the effect of drugs mediated by the gut microbiota and their metabolites on animals with CIA.…”
Section: Targeting the Gut Microbiota For The Treatment Of Ramentioning
confidence: 99%
“…Fecal SCFAs were quantified using gas chromatography-mass spectrometry (GC-MS) (Trace 1310-TSQ8000 Evo, Thermo, USA) following previous protocols (Shan et al, 2018;Luo et al, 2019). Briefly, gradient concentrations of acetate (ROE, USA), propionate (Dr. Ehrenstorfer, Germany), and butyrate (TCI, China) were prepared for standard curves.…”
Section: Gas Chromatography-mass Spectrometrymentioning
confidence: 99%